Alternate Clonal Dominance in Richter Transformation Presenting as Extranodal Diffuse Large B-Cell Lymphoma and Synchronous Classic Hodgkin Lymphoma. Issue 2 (1st August 2014) - Di Bernardo, Andrea; Mussetti, Alberto; Aiello, Antonella; De Paoli, Elena; Cabras, Antonello Domenico
Abstract: Objectives: Richter transformation (RT) represents the rare occurrence of a secondary aggressive lymphoma in the setting of chronic lymphocytic leukemia/small lymphocytic lymphoma (CLL/SLL). Methods: Here we describe the peculiar case of a patient with trisomy 12+ and atypical (CD5+, CD23−) CLL/SLL who developed a two-step RT with complex morphologic and molecular features. Results: Molecular analysis of a CLL/SLL population detected two different immunoglobulin rearrangement patterns corresponding to a main peak and a minor peak. Transformation took place both as gastric diffuse large B-cell lymphoma and as a synchronous bone marrow classic Hodgkin lymphoma with the same immunoglobulin rearrangement pattern corresponding to the minor peak detected in CLL/SLL at diagnosis. During chemotherapy, progression occurred as axillary nodal involvement by a CD5+ high-grade lymphoma with an immunoglobulin rearrangement pattern corresponding to the main CLL peak. Conclusions: In this case, the elaborate clinical and molecular picture may be correlated to an alternate dominance of two distinct clonal populations probably influenced by therapeutic and environmental factors.